Yogini - Temples of India Project Team (Jio Institute, 2024)
This is one of the many images of yoginis found at the site hinting towards a lost yogini temple compound. Contextualizing this image with several other relevant images suggests a maturity of Shakti and tantric traditions at the site. She is holding a cup in her left hand, often associated in tantric traditions with the cup containing the symbolic nectar of spiritual bliss attained after the completion of tantric sadhana. The two-armed yogini is seated in the lalitasana pose. She holds a mala in her right hand and a cup in her left hand. Her head is lost.